(untitled) (The Educator Journal, 2022)
The objective of this study, “Effectiveness of ICT tools in Science Education,” was to determine the current status of ICT use among secondary school students and teachers and to explore the problems while using the ICT tools. Simple random sampling was used as the sampling strategy. The instruments used to acquire the required data were student questionnaires and teacher interviews. I used a survey using descriptive data to achieve the study’s goals. Simple statistical tools such as frequency and percentage were used to assess the data. The descriptive technique was used as the analysis procedure for quantitative data. The findings and conclusions were drawn after a thorough review of the data. According to the findings, the participants preferred ICT tools, but there was a lack of information about how to use it. It was discovered that students frequently confront issues such as a lack of access to an e-library and a lack of understanding of computer capabilities. Teachers do not have sufficient ICT tools for teaching them also. There must be included ICT tools in the science curriculum. It is necessary to provide ICT tools, an appropriate time, and ongoing training to increase ICT abilities. It included recommendations for improving ICT in the classroom instructors and students